Online Learning during the COVID-19 Crisis from the Perspective of Students of Agricultural Sciences - Shawaqfeh, Samar (Dirasat: Educational Sciences, 2022)
Educational practices and strategies have changed due to the COVID-19 pandemic. Universities nowadays are adopting online education systems. This study aims to evaluate the experience of agricultural sciences students during the COVID-19 pandemic in Jordan with a focus on preparedness, attitude and barriers. An online survey was distributed to 559 students from four different majors at the College of Agriculture Sciences at Jerash University, Jordan. The results showed that there was a statistically significant difference in barrier, attitude, and preparedness scores between different age groups. The results indicate that about 76% of the students were satisfied with the quality of services offered from Jerash University during the COVID-19 lockdown. Students expressed a negative assessment of the practical courses being delivered online. This new experience for students during lockdown identified areas for improvement that can be worked on. Thus, sharing the study results could help to enhance online education with similar settings in colleges throughout the country..